Optimization of Drilling Parameters in Sisal-Human Hair Hybrid Composite Using Grey Relational Analysis - D. Elil Raja; S. Panneer Selvan; P. Prabhuraj; Tushar Sonar (Advances in Materials Science and Engineering)
Sisal is the most commonly used natural fiber in polymer composites due to its high strength, durability, and ability to stretch. In this present work, sisal and human hair were used as reinforcement for epoxy resin-based hybrid composites, and their effect on the mechanical properties was reported. Four composite plates with fiber volume fractions of 10%, 20%, 30%, and 40% were fabricated by the hand lay-up method. Chopped sisal fiber and human hair of 30 mm length were mixed with epoxy resin to fabricate the composites. In addition, high-speed steel (HSS) drills were used to study the influence of drilling parameters such as speed, feed, and drill point angle on the quality of the drilling. Three factors with three levels were considered for the design of the experiment. The drilling parameters were optimized using Grey Relational Analysis and the Taguchi method for the reduction of delamination. The experimental results indicate that a flexural strength of 38 MPa was achieved in a 60% epoxy, 20% sisal, and 20% human hair composite. NI vision assistant software was used to process the images taken on the drilled holes using the Matrix Vision camera. The optimization results showed that the feed rate played a pivotal role in deciding the delamination on the entry side of the hole. In contrast, the drill point angle significantly affects the delamination at the exit side of the hole. Better quality holes are achieved with a cutting speed of 2500 rpm and a feed rate of 50 m/min.